Wnt and Hedgehog Signaling Regulate the Differentiation of F9 Cells into Extraembryonic Endoderm - Deol, Gurjoth S. J.; Cuthbert, Tina N.; Gatie, Mohamed I.; Spice, Danielle M.; Hilton, Lindsay R.; Kelly, Gregory M. (Frontiers in Cell and Developmental Biology, 2017)
Mouse F9 cells differentiate into primitive extraembryonic endoderm (PrE) when treated with retinoic acid (RA), and this is accompanied by an up-regulation of Gata6. The role of the GATA6 network in PrE differentiation is known, and we have shown it directly activates Wnt6. Canonical Wnt/β-catenin signaling is required by F9 cells to differentiate to PrE, and this, like most developmental processes, requires input from one or more additional pathways. We found both RA and Gata6 overexpression, can induce the expression of Indian Hedgehog (Ihh) and a subset of its target genes through Gli activation during PrE induction. Chemical activation of the Hh pathway using a Smoothened agonist (SAG) also increased Gli reporter activity, and as expected, when Hh signaling was blocked with a Smoothened antagonist, cyclopamine, this RA-induced reporter activity was reduced. Interestingly, SAG alone failed to induce markers of PrE differentiation, and had no effect on Wnt/β-catenin-dependent TCF-LEF reporter activity. The expected increase in Wnt/β-catenin-dependent TCF-LEF reporter activity and PrE markers induced by RA was, however, blocked by cyclopamine. Finally, inhibiting GSK3 activity with BIO increased both TCF-LEF and Gli reporter activities. Together, we demonstrate the involvement of Hh signaling in the RA-induced differentiation of F9 cells into PrE, and while the activation of the Hh pathway itself is not sufficient, it as well as active Wnt/β-catenin are necessary for F9 cell differentiation.